The chloroplast genome of aromatic plants Cinnamomum burmanni (Lauraceae). Issue 2 (3rd July 2019) - Yang, Yanping; Song, Yu; Xin, Peiyao
Abstract: Cinnamomum burmanni (Nees et T. Nees) Blume is a valuable aromatic timber tree of the genus Cinnamomum Tree in the family Lauraceae. To better determine its phylogenetic location with respect to the other Cinnamomum species, the complete chloroplast genome of C. burmanni was sequenced. The total chloroplast genome size is 152, 775 bp, consisting of a pair of inverted repeats (IRa/b) with a length of 20, 092 bp separated by a large single-copy region (LSC) and a small single-copy region (SSC) which are 93, 687 and 18, 903 bp, respectively. The overall GC content of the cp genome is 39.1%. Further, maximum-likelihood phylogenetic analysis with K3Pu + F+I model was performed using eleven complete plastomes of the Lauraceae, which revealed that C. burmanni is closely related to C. verum .